M6A-Methylated circRAPGEF5 drives lung adenocarcinoma progression and metastasis via IGF2BP2/NUP160-mediated autophagy suppression - Liqun Ling; Tianqi Hu; Chenkang Zhou; Yingjie Dai; Lijuan Hu; Yuxin Chen; Zhaoting Hu; Kate Huang; Jie Chen; Yumin Wang (Molecular Cancer)
Abstract Background Lung adenocarcinoma (LUAD), the predominant histological subtype of non-small cell lung cancer, demonstrates critical regulatory involvement of RNA-binding proteins (RBPs) and circular RNAs (circRNAs) in tumorigenic processes. Emerging evidence highlights the circRNA-autophagy regulatory axis as a crucial modulator of cancer progression. This study systematically investigates the functional interplay within the RBP-circRNA-autophagy network in LUAD pathogenesis. Methods Employing RNA pull down, mass spectrometry and RNA immunoprecipitation facilitated the exploration of the circRAPGEF5 binding protein. M6A methylation RNA immunoprecipitation-PCR was utilized for m6A analysis. Immunofluorescence (IF) and fluorescence in situ hybridization (FISH) assays were conducted to ascertain the subcellular localization of target genes. Employing mRFP-GFP-LC3 fluorescent lentivirus labelling facilitated the monitoring of autophagy flow levels. Xenografts in mice were instrumental in affirming the role of circRAPGEF5. Results Through comprehensive molecular profiling, we identified elevated circRAPGEF5 expression in LUAD cells, which significantly suppressed autophagic flux while promoting malignant phenotypes including enhanced proliferation, migration, and invasion. Mechanistic investigations revealed that circRAPGEF5 directly interacts with the KH3-4 functional domain of Insulin-like Growth Factor 2 mRNA-Binding Protein 2 (IGF2BP2), an m6A reader protein. This interaction facilitated IGF2BP2-mediated stabilization of NUP160 mRNA, a nuclear pore complex component. Genetic ablation of NUP160 through RNA interference effectively restored autophagic activity, thereby attenuating the aggressive biological behaviors of LUAD cells. In vivo validation using xenograft models demonstrated that the circRAPGEF5/IGF2BP2/NUP160 signaling axis promotes tumor growth and metastatic dissemination through autophagy suppression. Conclusion Our findings reveal a novel epigenetic regulatory mechanism wherein m6A-modified circRAPGEF5 orchestrates autophagy inhibition via IGF2BP2-dependent stabilization of NUP160 transcripts, ultimately driving LUAD progression and metastasis. These results establish the circRAPGEF5/IGF2BP2/NUP160 axis as a potential therapeutic target for LUAD intervention.